2007
DOI: 10.2174/157016207780077020
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Tryptophan Metabolism via Serotonin in Ventricular Cerebrospinal Fluid in HIV-1 Infection Using a Neuroendoscopic Technique

Abstract: In this paper we report the study of tryptophan metabolism via serotonin in ventricular CSF in HIV-1 infection in order to investigate the origin of tryptophan metabolites in the human brain. The patients (n=4) were affected with non-communicating hydrocephalus. One of these also was suffering from HIV-1 infection. The CSF was withdrawn from different sites of the cerebral cavity with a neuroendoscopic procedure which allows an accurate exploration of all the cerebral ventricles. The measurement of tryptophan,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Elevated neopterin is consistently correlated with conversion of tryptophan to kynurenine, resulting in less serotonin synthesis. Plasma and CSF levels of serotonin are reduced in PWH [44][45][46] and greater tryptophan degradation (indexed by kynurenine/tryptophan ratios) has been linked to depression 20,47 and impulsivity/risk-taking 48 in PWH. In addition to serotonergic deficiencies, neopterin also correlates with decelerated conversion of phenylalanine to tyrosine, resulting in less dopamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated neopterin is consistently correlated with conversion of tryptophan to kynurenine, resulting in less serotonin synthesis. Plasma and CSF levels of serotonin are reduced in PWH [44][45][46] and greater tryptophan degradation (indexed by kynurenine/tryptophan ratios) has been linked to depression 20,47 and impulsivity/risk-taking 48 in PWH. In addition to serotonergic deficiencies, neopterin also correlates with decelerated conversion of phenylalanine to tyrosine, resulting in less dopamine synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin administration not only reduced the mortality rate from these viruses, but also significantly postponed onset of disease ( 10 ), providing further evidence of melatonin use as treatment in a number of viral diseases. There is some research concerning the effects of melatonin on retroviruses such as HIV and murine model retroviruses such as LP-BM5 and Ts1, though these do not seem to have many pertinent similarities to COVID-19 ( 32 , 33 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, disruption of cytoskeletal genes and dysregulation of somatostatin were found to be part of the pathologic process of major depressive disorder (MDD) in the setting of HIV (3). Tryptophan metabolism dysregulation is also suspected to play a role (4, 5).…”
Section: Introductionmentioning
confidence: 99%